Analysis of Bank Health During The Covid19 Pandemic in Indonesia, Using the Rgec Method - Siti Mar'atus; Agus Sukoco; Hepy Octalia Elfa Kolina (Jurnal Ekonomi, 2022)
This study aims to analyze the level of healthState-owned banks and private banks for the period 2018-2020 are viewed based on the overall RGEC (Risk profile, Good Corporate Governance (GCG), Earnings, Capital) aspects. This Type of Researchusing a qualitative approachtodataquantitative with research subjectsState-owned banks and private banks for the period 2018-2020. The data was obtained based on the document techniquementation. The data analysis technique used is the assessment of the soundness of the bankusing RGEC factors. Research resultfind that the soundness of the BankBUMN with (1) Risk Profile aspectusing the NPL ratio of "1.79%" gets the "Very Healthy" predicate, the LDR ratio of "118%" gets the "Unhealthy" predicate, (2) the GCG aspect with the composite "1" gets the "Very Good" predicate, (3 ) the Earnings aspect uses an ROA ratio of "2.51%" gets the "Very Healthy" predicate, the NIM ratio of "9%" gets the "Very Healthy" predicate, the BOPO ratio of "-131%" gets the "Very Healthy" predicate, ( 4) the “17%” CAR aspect gets the “Very Healthy” predicate. Meanwhile, at the Bank's soundness level,Private with (1) Risk Profile aspekusing the NPL ratio of "-5%" gets the "Very Healthy" predicate, the LDR ratio of "101%" gets the "Unhealthy" predicate, (2) the GCG aspect with a composite of "2" gets the "Good" predicate, (3) the Earnings using an ROA ratio of "2.25%" gets the "Very Healthy" predicate, the NIM ratio of "30%" gets the "Very Healthy" predicate, the BOPO ratio of "524%" gets the "Unhealthy" predicate, (4) aspects CAR "11%" received the title "Very Healthy". In general, the soundness of banks in the period 2018-2020State-owned bankreceived the "very healthy" predicate with a composite value of "103%", while private banks received the "fairly healthy" predicate with a composite score of "60%"